Efforts to Improve the Ability to Read the Qur'an through the Use of the Qira'ati Method in Class V Students of SD Negeri 02 Teratak Teleng - Ernita (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve students' ability to read the Qur'an in Islamic religious education learning by using the qira'ati method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data of this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the qira'ati method can improve the ability to read the Qur'an in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 48.71%, the first cycle 66.39% and in the second cycle increased to 89.66%. Thus, the use of the qira'ati method can be used as an alternative to improve students' ability to read the Qur'an in Islamic religious education learning.